New species and new records of the leafhopper genus Aguriahana Distant (Hemiptera: Cicadellidae: Typhlocybinae) from China - Huang, Min; Zhang, Yalin (Zootaxa, 2011)
Nine new species of Aguriahana Distant are described and illustrated: A. digitata, A. singularis, A. simplex, A. longicorna, A. tripoda, A. recticornis, A. furcata, A. dilatata and A. recurva spp. nov. Three previously described species, A. uncinata (Vilbaste), A. paivana (Distant) and A. distanti Dworakowska are newly recorded from China. A checklist and key to the 34 species known from China are provided.